A universal fluorescent lateral flow strip approach based on molecular beacon-assisted rolling circle amplification for point-of-care nucleic acid detection - Xiaopeng Chen; Wentao Wang; Pin Zhang; Qionglin Wang; Kangbo Liu; Fengfang Ding; Xianwei Zhang; Ligong Hou; Yingyu Zhang; Wancun Zhang (Sensors and Actuators Reports, 2025)
Simple, cost-effective, sensitive, and specific approaches that are capable of enabling point-of-care testing (POCT) are crucial for clinical diagnosis, especially in settings with extremely limited resources. Therefore, a universal, simple, low cost, sensitive, and specific POCT approach called RCA-F-LFS was developed by combining molecular beacon (MB)-assisted rolling circle amplification (RCA) for target amplification with fluorescent lateral flow strips (F-LFS) to enable highly sensitive and visual detection of RCA products. Using Mycoplasma pneumoniae as the detection target, RCA-F-LFS demonstrated high sensitivity (0.1 pM) and specificity, accurately distinguishing it from other pathogenic microorganisms. In addition, RCA-F-LFS enables visual detection of both Mycoplasma pneumoniae DNA and RNA. The detection results of clinical throat swab samples showed that RCA-F-LFS could accurately detect Mycoplasma pneumoniae, with 100 % agreement with current clinical approaches. As a proof of concept, RCA-F-LFS can detect other nucleic acid targets by simply changing the target sequence, offering a robust and versatile strategy for the development of novel clinical POCT detection methods.